"Breastfeeding in public" for incarcerated women: the baby-friendly steps - Martha Jane Paynter; Erna Snelgrove-Clarke (BMC, 2019)
Abstract Background Women are the fastest-growing population in carceral facilities in Canada. Most incarcerated women are mothers, with above-average parity. The incarceration of women has implications not only for women's health, but for that of their children. For example, how is breastfeeding and access to human milk supported in the context of imprisonment? Both carceral and health services are publicly-funded and administered in Canada. Due in part to the well-documented ill-health burden of imprisoned women, health and carceral functions overlap in the spaces of confinement. This paper discusses "breastfeeding in public" in relation to imprisoned women: separated from the public, yet in publicly-funded spaces under public servant control. With increasing adoption of Baby Friendly Hospital Initiative (BFI) Ten Steps in Canadian health centres, there is a need to consider the health centre spaces precluded from its application and make visible the women and children affected. This paper uses the BFI Steps as a lens to consider the environment of confinement for the breastfeeding incarcerated person. The exclusion of breastfeeding and access to human milk for imprisoned women and children extends the punitive carceral function beyond the experience of incarceration and beyond the experience of the convicted mother. Discussion Carceral facilities lack breastfeeding policies, foundational to breastfeeding support. Despite high fertility and parity among incarcerated women, carceral health care providers are not required to demonstrate maternity and reproductive health care specialization. The overarching mission of carceral institutions remains security, and support for breastfeeding among incarcerated women is hampered in spaces of conflict, punishment, surveillance and control. A minimal requirement to support exclusive breastfeeding is to promote the mother being with the infant and most incarcerated mothers are separated from their infants. Incarcerated women lack support, information, and community connections for extended breastfeeding beyond six months. Carceral facilities are not welcoming environments for breastfeeding families. Despite the incompatibility of breastfeeding with incarceration, BFI Step 10, coordinating discharge, demonstrates opportunity for improvement through community and health care provider engagement. Conclusion Incarceration challenges the reach and applicability of the BFI Steps to enhance breastfeeding and to problematize the idea of breastfeeding "in public."